THE SUSCEPTBILITY OF SOME BARLEY CULTIVARS TO ROOT ROT INFECTION AND ITʼS BIOLOGCAL WITH MYCORRHIZA AND CHEMICAL CONTROL - Ali Al kubicy (Mesopotamia Journal of Agriculture, 2019)
This study aimed to biological and chemical control for the most important root rot disease on barley in Iraq. Seven barley culivars were tested to barley root rot pathogens showed that all the cultivars have root rot infections and Iba cuv. has been the lowest level (0.45) in the greenhouse. At the field, All the cuvs. also have shown the infection of root rot and Al- Jazerah cuv. has the lowest class under natural conditions. Also, this cuv. characterized by an increase in the flag leaf (10.93cm2) and produced a greater number of spikes (2.13 spike / plant) and the highest rate of dry weight (4.53 gm/plant). The local Aswad cuv. characterized with the high content of salsilic acid (1.03%). Using the Veiscular Arbsuculur Mycorrhiza (VAM) fungus (Glomus intradices) has shown a decrease in the infection of two barley classes (Jazerah and Zanbaca) by root rot and in improving some characteristics of barley classes under the conditions of industrial infection which reflects on improving some plant characteristics in the greenhouse. At the field, Glomus intradices were efficient in decreasing the disease sevenity of barley root rot (0.34) which was morally equivalent to the best Fungicide (Vitavax) (0.65),This reflects on some plant characteristics and on the barley productivity. Thus, the productivity has increased from 697.3 to 1313.5 ton/hectare.fungicide. Under the industrial conditions of infection in the greenhouse, the fungicide (Vitavax and Raxil) had been the best for controlling disease and improving some characteristics of barley, followed by Mancozeb and Dividend. At the field, the pesticide (Vitavax) had shown superiority in decreasing the disease severity from 0.65 to 0.29 and improving some yield characteristics and raising the productivity from 697.3 to 1268 ton/hectare as well as the pesticide  Mancozeb which raises productivity from 697.3 to 1340.5 ton/hectare.